Prioritization of Agro-industrial By-products for Improved Productivity on Smallholder Dairy Farms in the Lake Victoria Crescent, Uganda - Atuhaire, Andrew M.; Mugerwa, Swidiq; Okello, Samuel; Lapenga, Kenneth; Kabi, Fred; Lukwago, George (Frontiers in Science, 2014)
Livestock feed fluctuations in quality and quantity is a major constraint to dairy cattle production in Uganda, particularly, in smallholder dairy cattle production. Studies on prioritizing agro-industrial by-products in dairy cattle feeding are central to formulation of sustainable feed management strategies. This study was thus conducted to investigate farmers’ knowledge of agro-industrial by-product management as dairy cattle feed to build logical ideology required in development of appropriate feed management strategies. Focus group discussion and individual interviews were conducted in Lake Victoria Crescent agro-ecological zone to capture information on farmers’ knowledge of the factors enhancing agro-industrial by-products utilization, temporal and spatial variability, and limitations to utilization in smallholder dairy farming system. Chi-square test at p<0.01, df = 3 showed a significant difference among farmers rankings of utilization and factors limiting utilization (p<0.01, df = 4) of agro-industrial by-products across all the study districts. There was no significant difference (p>0.05) in spatial and temporal variability of agro-industrial by-products. The study provided basic information about farmers’ knowledge on importance of agro-industrial by-products that could aid the development of sustainable and socially acceptable dairy cattle feed management strategies.
Keywords: By-product; Dairy cattle; Farmers knowledge